BIOLOGICAL FEATURES AND SOWING QUALITIES OF NON-CLOTTING GARLIC, DEPENDING ON THE LOCATION OF THE GARLIC CLOVES IN THE BULB - A. I. Кilinchuk; V. F. Botnari (Овощи России)
Research conducted at the Institute of Genetics, Physiology and Plant Protection found that when using the peripheral and internal cloves of garlic for planting in comparison with the use of them of different locations without calibrating them by mass, during the growth between the variants differences in the area of the leaf surface of plants were observed. Indicator of the foliage also depends on of the location of the garlic cloves in the bulb. The location of garlic cloves, peripheral and internal, as a planting material, also affects the growth of vegetative mass formation and bulb weight. In the bulb structure the peripheral cloves of garlic have some increase in their quality over internals (the ratio is in the range of 60:40%). Analysis of the obtained productivity data makes it possible to note that in the formation of high yields of non-clotting garlic, the location of the clove of garlic in the bulb is of the leading importance. Differences in gross and commodity yields, between variants (B3) and (B2) are not so great, but the advantage of the first one is everywhere traced. Studies have also found that the use of all garlic cloves for planting at different locations without calibrating them by weight, leads to differently bulbs maturing time, which makes the harvesting process more difficult and leads to additional labor costs, in which case when harvesting - 24% of it consist of small noncommodity bulbs. The use of the same mass garlic cloves of different locations for planting ensures the simultaneous of ripening, a greater proportion of standard bulbs and a high quality of planting material.